Kogrog: The Collective Process of Painting in a Kaingang Basket - Souza, Sheilla P. Dias de; Neri, Maria Vitória; Glicério, Sanda Kokrog Ninvaia; Jesus, Raquel Rodrigues de (Farol, 2022)
This text was written from methodologies associated with decolonialism in the arts, the concept of epistemicide, research in arts and autoethnography, with which we sought to promote a collective creation among students of Visual Arts and Kaingang professors. It is an analysis of a painting collectively made on a Kaingang basket, with the aim of sharing different experiences and promoting greater knowledge about Kaingang culture without taking away the indigenous role.